2015
DOI: 10.1097/phh.0000000000000331
|View full text |Cite
|
Sign up to set email alerts
|

The Public Health Workforce Interests and Needs Survey

Abstract: This article describes a nationally representative survey of central office employees at state health agencies to characterize key components of the public health workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 36 publications
2
116
1
2
Order By: Relevance
“…In terms of research methods, we can see that a questionnaire survey is the main approach used to obtain the data related to employee training. Other methods, such as structural equation modelling, among others, are also used together to analyse employee training [44,52,54,55]. It is obvious that the majority of studies on employee training are based on qualitative analysis, and quantitative analysis is less used to analyse training programmes.…”
Section: Employee Trainingmentioning
confidence: 99%
“…In terms of research methods, we can see that a questionnaire survey is the main approach used to obtain the data related to employee training. Other methods, such as structural equation modelling, among others, are also used together to analyse employee training [44,52,54,55]. It is obvious that the majority of studies on employee training are based on qualitative analysis, and quantitative analysis is less used to analyse training programmes.…”
Section: Employee Trainingmentioning
confidence: 99%
“…Several authors have examined the current and future needs of the governmental public health workforce and future trends impacting the governmental public health system. 1 – 7 The Institute for Alternative Future's Public Health 2030 Scenarios aptly describe 4 potential futures that public health agencies may face (Table 1 ), and several of these scenarios would have negative impact on SHA capacity to address public health challenges and improve population health. 8 Brownson and Kreuter described future trends impacting public health in the new millennium in 1997.…”
Section: Beyond the Status Quomentioning
confidence: 99%
“…Policy development and public health advocacy have been identified as 2 of the greatest needs of the public health workforce. 1 A tactic to promote the strategic move from patients to policies is to prioritize training and competency development in public health policy and advocacy. The public health leaders of the future should be as competent in policy development as they are in the public health sciences.…”
Section: Strategic Move 3: From Patients To Policiesmentioning
confidence: 99%
“…The predominant finding of all these papers was the very close relation between job satisfaction and the variables of organizational structure (Almalki, FitzGerald, & Clark, 2012;Baldwin, Lyons, & Issel, 2011;Best & Thurston, 2006;Campbell, Foweles, & Weber, 2004;Cumbey & Alexander, 1998;Curtis & Glacken, 2014;Graham, Davies, Woodend, Simpson, & Mantha, 2011;Haugh & Laschinger, 1998;Keller, Strohschein, Lia-Hoagberg, & Schaffer, 1998;McMaster University School of Nursing and the Health Services Research Unit, 2009;Yamashita, Takase, Wakabayshi, Kuroda, & Owatari, 2009). The 21st-century studies have reported relatively low levels job satisfaction among public health nurses and emphasize the need for additional research on job satisfaction among public health workforce (Curtis & Glacken, 2014;Graham et al, 2011;Hilliard & Boulton, 2012;Sellers et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%